A Global Public Health Perspective: Facilitating Access to Assistive Technology. Issue 9 (September 2018) - du Toit, Rènée; Keeffe, Jill; Jackson, Jonathan; Bell, Diane; Minto, Hasan; Hoare, Philip
Abstract : SIGNIFICANCE: Clinicians should not overlook vulnerable populations with limited access to assistive technology (AT), the importance of collaboration in multidisciplinary teams, advocacy for enabling environments, and supportive health systems. Resources, a model of care, and recommendations can assist clinicians in contributing to changing attitudes, expanding knowledge, and improving the lives of many. The increasing availability of innovative advances in AT can immeasurably enhance the quality of life of people with disabilities. Clinicians will undoubtedly welcome the prospect of having cutting-edge AT available to prescribe to individuals who consult them. Arguably, though, the development of innovative strategies to improve access to AT, especially to underserved people "left behind, " is equally urgent. Current efforts are inadequate, with millions of people with disabilities not being reached. Particularly at risk are women, children, and the elderly, as well as poorer people who live in resource-poor and remote areas, especially in low- and middle-income countries. Not only must physical access be facilitated, but also quality services must be available. Good-quality, affordable AT, which is appropriate and acceptable to the user, would ideally be provided by competent personnel, working in multidisciplinary teams, offering comprehensive, person-centered services, including rehabilitation, fully integrated into the various levels of the health system. Clinicians can contribute to improving access to quality services, participate in initiatives aiming to increase the knowledge of health personnel and the public, engage in advocacy to change attitudes, influence legislation, and raise awareness of universal health coverage—ultimately facilitating access to AT for all.